Geometrical integrity of microholes produced by micro-EDM - Ali, Mohammad Yeakub (Research Management Center, IIUM, 2008)
Although there are many techniques for the fabrication of micro-hole for Bio-MEMS and microfludic applications, characterization of high aspect ratio (depth/diameter) micro-hole is a critical issue among the researchers worldwide. The characteristics such as surface finish, vertical side wall, etc. influence the fluid flow inside the channels. This project (EDW-17) was followed by project of EDW-18, where EDM micro drilling process was developed. In this research project the high aspect ratio EDM drilled micro holes were measured and investigated. At first, an experimental process was developed to open the internal geometry of the holes and then characterized the geometrical integrity and surface texture using scanning electron microscope (SEM) and atomic force microscope (AFM).